Law Enforcement Against Obstruction Of Justice In Eradicating Criminal Acts Of Corruption in Indonesia - Yamin, Muhamad; Bawono, Bambang Tri (UNISSULA Semarang, 2025)
Indonesia is a country based on law that is not based on mere power. The terminology of the rule of law used by Indonesia is neither rechtsstaat nor rule of law, because the two terms contain meanings that are not identical to the characteristics of Indonesia where rechtsstaat contains the meaning of a country that has a purely continental legal system, while in judicial practice it adopts dissenting opinion decisions. This research is a normative legal research that starts from a legal issue. According to its characteristics, legal issues are very different from social issues as phenomena of social research objects, so that the approaches used are also unique. Legal research is not social science research and legal research does not recognize data. The positive legal regulations in Indonesia regarding the Criminal Act of Obstructing the legal process or what is known as Obstriction of Justice are divided into two, namely: Regulations regulated in general criminal law as regulated in the Criminal Code (KUHP), and Regulations regulated in Special Criminal Law, such as the Corruption Crime Law. The crime of obstructing the judicial process or what is known as Obstruction of Justice as regulated in Article 21 of Law Number 31 of 1999 concerning the Eradication of Corruption as amended by Law Number 20 of 2001 can be qualified as a formal crime (formeel delict), meaning that it does not require that the act has indeed resulted in a legal process being obstructed/hampered by the perpetrator's actions. but only requires the existence of the perpetrator's intent or intention to obstruct the legal process.